Water Quality Measurement in Illegal Gold Mining Areas Using Sentinel-2A MSI Satellite Images of the Batanghari River, Tebo Tengah District - Sinaga, Baginda; Kurniawan, Robert (Politeknik Statistika STIS, 2025)
Water quality in Indonesian rivers has declined due to pollution from solid and liquid waste from industrial and domestic sources. The Batanghari River, the longest river on the island of Sumatra, faces various environmental problems, including pollution from illegal mining activities. Artisanal and small-scale gold mining (ASGM) contributes to mercury release, contaminating water and soil and posing health risks to communities. Conventional monitoring methods have limitations in coverage and efficiency. Therefore, this study utilizes Sentinel-2A MSI satellite imagery to assess and map water quality conditions around illegal gold mining areas along the Batanghari River in Tebo Tengah District. The developed model uses K- Means, Fuzzy C-Means (FCM), Principal Component Analysis (PCA), and Weighted Arithmetic Water Quality Index (WAWQI) to extract water quality features. The findings indicate that WAWQI provides a more representative quantitative assessment, revealing that areas near illegal gold mining sites in Batanghari river exhibit moderately to heavily polluted water quality. This approach is expected to support water quality monitoring and assist policymakers in managing water resources and the environment.